Variasi Bahan Komposit Edible Coating Pati Talas-Karagenan Dan Konsentrasi Gliserol Terhadap Karakteristik Buah Salak Kupas - Patandianan, Dimas Lomo; Hartiati , Amna; Harsojuwono, Bambang Admadi (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Salak pondoh is one type of salak that is very popular because it has a sweet and crunchy taste even though it is picked before it enters its harvest age. The increasing public awareness of the importance of consuming healthy food amidst the lack of time constraints in serving encourages opportunities for peeled salak processing. In the peeled state, salak will deteriorate faster due to the loss of the skin layer. One of the efforts that can be done to inhibit the process is the application of edible coating. This study aims to determine the effect of taro-carrageenan starch combination and glycerol addition on the characteristics of salak pondoh fruit and to determine the right combination of taro-carrageenan starch and glycerol addition on the characteristics of salak pondoh fruit during storage. This study used a factorial Randomized Group Design (RAK) with two treatment factors. The first factor is the combination of taro starch-carrageenan consisting of 3 levels namely P1 (25:75), P2 (50:50), P3 (75:25), and the second factor is the addition of glycerol consisting of 3 levels namely G1 (1g), G2 (2g), and G3 (3g). Each treatment was repeated 2 times with a storage period of 9 days. The parameters observed in this study were weight loss, total soluble solids, vitamin C, total acid and organoleptic. The results showed that the combination of taro starch-carrageenan and glycerol addition had no significant effect on weight loss, total soluble solids, vitamin C, and total acid of salak pondoh during 9 days of storage. Based on the organoleptic test, the variation of taro starch-carrageenan 50:50 and the addition of 1g glycerol is the treatment that gives the best coating results for 6 days of storage with a taste value of 3.20, color 3.73, aroma 3.47 and hedonic value 5.13.